Analisis Performa Frontend Website Menggunakan Web Vitals Pada Halaman Community Yayasanmangroveindonesia.com - najoan rizki; Reisa Permatasari; Abdul Rezha Efrat Najaf (PPPM Institut Teknologi Pagar Alam, 2026)
Frontend performance is a critical factor influencing website user experience, particularly in terms of page loading speed, visual stability, and rendering efficiency. This study aims to analyze the frontend performance of the community page on yayasanmangroveindonesia.com using the Core Web Vitals approach supported by two widely used automated testing tools, namely Google Lighthouse and GTmetrix. A descriptive quantitative method was employed by conducting performance testing three times on each tool, and the results were averaged to obtain more representative measurements. The evaluation focused on the metrics available in both tools, including Largest Contentful Paint (LCP) and Cumulative Layout Shift (CLS) as the primary metrics, supported by First Contentful Paint (FCP), Total Blocking Time (TBT), Speed Index, and Time to Interactive (TTI). The results show that Google Lighthouse achieved a Performance Score of 95, with an average LCP of 2.77 seconds, CLS of 0.03, FCP of 0.97 seconds, TBT of 56.67 ms, and Speed Index of 1.23 seconds. Meanwhile, GTmetrix obtained a Performance Score of 99 and a Structure Score of 100, with an average LCP of 0.48 seconds, CLS of 0.06, FCP of 0.48 seconds, TBT of 5.33 ms, and TTI of 0.66 seconds. Overall, the website demonstrates good frontend performance, although the LCP value measured by Google Lighthouse slightly exceeds the recommended Core Web Vitals threshold, indicating opportunities for further optimization. The findings suggest that combining Google Lighthouse and GTmetrix provides a more comprehensive performance evaluation and can serve as a reference for implementing frontend optimization strategies to improve user experience.